Nurses’ perceptions about management practices of nurse managers during pandemics: a descriptive and cross-sectional study - Tisinli, Ayla; Saydamlı, Şeyda (ABCS Health Sciences, 2024)
Introduction: Hospitals may not be able to manage the chaotic environment during pandemics through classical management principles. Management can only be achieved with the help of effective leadership, appropriate flow of crisis management systems, teamwork, and collaboration. Nurse managers should have effective management skills. Objective: To evaluate the perception of the nurse managers’ practices by nurses such as resource management, organization, communication, psychosocial, care-training, and decision-making practices in the management of the pandemic based on the COVID-19 pandemic. Methods: A quantitative, cross-sectional method was used, and a web-based online questionnaire was applied to collect data. This study included 182 nurses working in a public and private hospital in İstanbul. Result: The nurses perceived the management practices of their managers at a moderate level. The leaders’ resource management practices as low (16.5%), and medium (78.6%) perceive. There was a statistically significant difference (p<0.01) between the communication and team relations (p<0.05), resource management (p<0.01), care-training (p<0.05), and decision-making scores (p<0.01) of the nurses working in the private hospitals compared to those working in the public hospital. Conclusion: To effectively manage a complex and chaotic environment, nurse managers should trust their team, have speed and adaptation skills, be based on human factor principles, and provide a safe working environment. Education should be emphasized so that nurses can work in specialized areas and nurse managers can improve their management skills.